(untitled) (Journal of Misan Researches, 2024)
This study emphasizes the wife’s entitlement to inherit from her deceased husband’s estate, a right mandated by God in the Holy Quran. However, the doctrinal disagreement revolves around her deprivation of non-movable assets such as land, goods, and crops—a matter specifically addressed by Imami jurisprudence, differing from other Islamic schools of thought. Given the study’s significance, it has been scrutinized by jurists, researchers, and academics, with ongoing debate among scholars regarding the legal adaptation to the nature and mechanism of this deprivation. Our study aims to address and discuss these issues using a contemporary legal approach, yielding results that the researcher seeks to present for practical implementation.